Emergency Medical Service Responders’ Perspectives on Transgender, Intersexual, and Non-Binary Patients in Germany - Torben Brod; Kambiz Afshar; Christoph Schroeder; Carsten Stoetzer; Stephanie Stiel (Western Journal of Emergency Medicine)
Introduction: Gender minorities, including transgender, intersexual and non-binary (TIN) individuals, are at risk of receiving suboptimal care in emergency departments due to clinicians’ limited knowledge and formal training in TIN-specific needs. Little evidence is available regarding emergency medical service (EMS) responders, including paramedics (EMT-P), emergency medical technicians (EMT) ,and prehospital emergency physicians (EP). Therefore, in this study we aimed to explore the experiences and knowledge, attitudes, and education/training needs of EMS professionals in Germany regarding the care of TIN patients. Methods: In April 2023, we electronically surveyed EMTs, EMT-Ps and prehospital EPs from ambulance stations across Germany. Participants completed a questionnaire consisting of 15 closed-ended items assessing their experience and knowledge, attitudes, and education/training needs regarding the care of TIN patients. We used standard descriptive statistics and tested for group differences using the chi-square test. Results: Of the 2,925 potential respondents, 906 completed the survey and were eligible for further analysis (response rate: 31%). Of these, 218 (24%) were prehospital EPs and 688 (76%) were EMTs and EMT-Ps, the latter two being significantly younger and less experienced. Almost half of the respondents reported having experience in caring for TIN patients as EMS responders (45% of EMTs/EMT-Ps vs 40% of prehospital EPs) but demonstrated significant gaps in non-medical and medical knowledge. Attitudes toward TIN patients were generally positive, but there were discrepancies between perceived comfort and actual communication behavior, with up to 25% of respondents overall avoiding questions they would ask non-TIN patients. Most respondents had no formal training in the appropriate management of TIN patients: only 7% of EMTs/EMT-Ps and 5% of prehospital EPs indicated having received such training during their professional or medical training. Our survey showed that 63% of EMTs/EMT-Ps and 62% of prehospital EPs agreed that there is an urgent need to increase awareness for TIN patients among EMS responders. Conclusion: Despite generally positive attitudes toward transexual, intersexual and non-binary patients, EMS responders in Germany demonstrated deficits in knowledge and clinical preparedness to care for this vulnerable patient population, indicating that the care of TIN patients has not yet become routine in EMS and highlighting a strong need for improved education and training.